BLOG INTERAKTIF BERBASIS LITERASI DIGITAL SEBAGAI MEDIA KAMPANYE MODERASI BERAGAMA BAGI GENERASI MILENIAL - Jenri Ambarita; Ester Yuniati (Tatar Pasundan: Jurnal Diklat Keagamaan, 2021)
This research aims to develop an interactive blog based on digital literacy as a campaign medium for religious moderation of millennial generation. This research is a Research and Development (RnD) ADDIE model with the stages of Analysis, Design, Development, Implementation and Evaluation. The validation or due diligence of interactive blog is carried out by media experts, material experts, and practitioners. The interactive blog trial was carried out in two stages: a small group trial consisting of 10 Early Childhood Christian Education students and a large group trial involving 55 Christian Religious Education students. For the blog feasibility assessment, media experts gave an average score of 4.5 which lies in Very Good category and material experts gave 4.00 which is included to the Good category as well. At the small group trial stage, the average value was 4.15 and the large group trial was 4.14, both in Good category. Thus, it can be concluded that interactive blog is quite feasible to be used as a medium for religious moderation campaigns based on digital literacy of millennials.Keywords: interactive blog; digital literacy; religious moderation; millennial generation